Kesiapan Mahasiswa dalam Pembelajaran Daring dan Hubungannya dengan Hasil Belajar - Dewi Wardah Mazidatur Rohmah; Muhammad Dhika Arif Rizqan (Universitas Muhammadiyah Surakarta, 2021)
Universitas Terbuka (UT)-or Open University- has been organizing Pendidikan Tinggi Jarak Jauh (PTJJ)-Distance Learning for Higher Education- since 1984. Along with the changing era, PTJJ has integrated the use of online technology with the aim that UT students can conduct the learning process through online media. The present study aims to measure the level of readiness of UT students in online learning after they received the EKBM (Edukasi Kegiatan Belajar Mandiri) lecture and how this readiness affects the results of UT students learning outcomes. The researchers applied a quantitative method in this study. The data were collected through a survey. The respondents were 350 UT students from various majors such as Public Administration, Accounting, Sharia Accounting, Sharia Economics, Communication Study, Librarianship, Management, and Primary Education. The findings showed that Sharia Economics students have a high readiness score while the Management students have a low readiness score. Unexpectedly, these Sharia Economics students have low learning outcomes. Meanwhile, Management students have high learning outcomes. It seemed that the students’ high readiness score in online learning outcomes could not guarantee the students learning outcomes.